Discourse Analysis of Rape News in Pesantren on Online Media - Eka Anjani; Noval Amin (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
Abstract Media is a product of ideology and has a significant role in public understanding of certain events. Online media such as Kompas.com and Detik.com are popular media today, They publish about rape case committed by Herry Wirawan. The purpose of this research is to analyze the online media Kompas.com and Detik.com related to the coverage of rape cases from the perspective of social construction. The research method used is library qualitative with Zhong Dang Theory of Framming and analytical methods in the form of data reduction, data classification, and data analysis. the results of his research show that Detik.com seeks to encourage the judicial process so that Herry Wirawan is given severe punishment, especially castration punishment, while Kompas.com constructs Herry Wirawan's behavior as a depraved crime that should be reported to the public, so that the community oversees the judicial process so that it runs objectively and criticizes the police regarding the case was not made public from the start.